Research on Virtual Education, Inclusion, and Diversity - Marlene Fermín González (Athabasca University Press, 2019)
This article covers a topic related to increases in the existing heterogeneity of the university student population, specifically in virtual learning environments. There is a growing concern for offering training alternatives that include all students. As the first step in a line of research related to quality, equity, and inclusion in e-learning, we aim to identify emerging trends in research on inclusive virtual education (IVE) at the higher education level and how inclusion is conceptualized. Our goal is to provide ideas on future research topics and raise issues for further exploration. This research was conducted through a systematic review of articles published in the last decade in the WOS and Scopus databases. Upon reflection, we suggest the need for inclusive e-learning educational designs with greater emphasis on human diversity in all of its complexity. By doing so, we may be able to contribute to increasing the equality of educational opportunities and overcoming the barriers that restrict the access, continuity, and successful exit of the entire student population, regardless of their individual learning needs.